(x-4)*(x-6)-х*(х-10)

2
Ответов - 1
(x-4)*(x-6)-х*(х-10)

Вопрос задал ученик
Категории: Математика

Ответы


Гость
(x-4)*(x-6)-x*(x-10)=x²-6x-4x+24-x²+10x=24
(x-3)*(x-7)-2x*(3x-5)=x²-7x-3x+21-6x²+10x=-5x²+21
2c*(3c+4)-2c*(4+3a)=6c²+8c-8c-6ac=6c²-6ac=6c(c-a)
(y+10)*(y-2)-4y*(2-3y)=y²-2y+10y-20-8y+12y²=13y²-20
3a*(2a-1)-2a(4+3a)=6a²-3a-8a-6a²=-11a
Добавить ответ
Похожие вопросы
Топ Комментарии Архив
«    Октябрь 2020    »
ПнВтСрЧтПтСбВс
 1234
567891011
12131415161718
19202122232425
262728293031 
Теги